Cechy równoboczności trójkątów - Górowski, Jan; Łomnicki, Adam (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
The paper presents some non-standard (in the sense: not yet presented in the literature), necessary and sufficient conditions for a triangle to be isosceles.